2015
DOI: 10.1302/0301-620x.97b10.35668
|View full text |Cite
|
Sign up to set email alerts
|

The five-year radiological results of the uncemented Oxford medial compartment knee arthroplasty

Abstract: This study reports on the first 150 consecutive Oxford cementless unicompartmental knee arthroplasties (UKA) performed in an independent centre (126 patients). All eligible patients had functional scores (Oxford knee score and high activity arthroplasty score) recorded pre-operatively and at two- and five-years of follow-up. Fluoroscopically aligned radiographs were taken at five years and analysed for any evidence of radiolucent lines (RLLs), subsidence or loosening. The mean age of the cohort was 63.6 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…In a recent study on 150 consecutive cementless UKAs, Hooper et al [ 15 ] were able to demonstrate a significant improvement according to the High Activity Arthroplasty Score following UKA (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study on 150 consecutive cementless UKAs, Hooper et al [ 15 ] were able to demonstrate a significant improvement according to the High Activity Arthroplasty Score following UKA (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of seventeen studies used validated activity scores to evaluate the pre- and post-operative level of physical activity. Ten of these studies reported a statistically significant improvement following UKA according to the UCLA activity score [ 51 ], the Tegner activity score [ 38 ] or the High Activity Arthroplasty Score [ 1 , 10 , 15 , 18 , 21 , 26 , 30 , 44 , 45 , 47 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone-implant partial radiolucency was 7% and complete radiolucency was 0% in the cementless cases compared with 65% and 29%, respectively, in the cemented group. Hooper et al 44 independently confirmed these results. In a large multicenter study of more than 1000 knees undergoing cementless Oxford UKA, implant survival was 97.2% at 6 years with no increased complication rate compared with cemented UKA.…”
Section: Cemented Ukamentioning
confidence: 81%